ITG 1000, Risk Detection and Accounting Information: a Theoretical Analysis on the Cost versus Benefit for Micro and Small Enterprises - Mateus Alexandre Costa dos Santos; Luiz Carlos Marques dos Anjos; Paulo Roberto Nóbrega Cavalcante; Paulo Aguiar do Monte (BBR: Brazilian Business Review)
This essay aims to discuss aspects related to the incentives that individuals face with regard to the adoption or not of ITG 1000, as well as the possible scenarios resulting from the responses of these individuals to such incentives. It was assumed as a basic premise that there is no executive inter-relationship between keeping only the cash book ledger, or adopting ITG 1000, and other economic choices. The discussion is based on the assumptions of economic rationality and assumes that individuals, under uncertainty, will behave in a manner attributable to Von Neumann-Morgenstern. In addition, it was guided by the classical model proposed by Allingham and Sandmo (1972), referring to the economic theory of tax evasion. It may be noted that the successful adoption of ITG 1000 can be achieved with an awareness of the segments involved and with the prohibition and penalizing of adverse behavior, permitting one to infer that the adoption of the 1000 ITG is much more dependent on the accounting class’s actions, rather than a management decision itself.